Research methods for the diagnosis of soil fertility problems - Wortmann, Charles S.; Regassa, T; Mughogho, SK (Southern Africa Development Coordination Conference (SADCC), 1988)
The 3 stages of the diagnostic procedure to identify soil fertility problems are reviewed, namely (1) classification of land into soil fertility management units, (2) diagnosis of soil fertility and plant nutrition problems, and (3) determination of the causes and mechanisms of nutrient disorders. In the 1st stage, the criteria used in grouping the land may include natural vegetation, common crops and management practices, topography, climate, geology, and soil physico-chemical properties. Different classification systems used are briefly indicated, in particular the Fertility Capability Classification System (a technical system of grouping soils according to the kinds of problems they present for the agronomic management of their chemical and physical properties). In the 2nd stage, diagnosis can be made by the visual observation of symptoms expressed by plants, by chemical tissue analysis, by chemical soil analysis, and through nutritional screening expt. The 3rd stage, just introduced, will help develop effective management practices, such as the use of artificial fertilizers or amendmentes, phosphate rock, green manure crops, or agroforestry. A detailed list is included of bean plant symptoms indicative of nutritional disorders. (CIAT)